The complete chloroplast genome of the traditional Chinese herb, Uncaria rhynchophylla (Rubiaceae) - Li-Zhen Ling; Shu-Dong Zhang (Mitochondrial DNA. Part B. Resources, 2020)
Uncaria rhynchophylla is a vine plant belonging to the family Rubiaceae and has been used as medicine for a long time in China. In this study, the complete chloroplast (cp) genome sequence of U. rhynchophylla was first reported and characterized. The cp genome was 154,605 bp in length and contains a pair of inverted repeats (IRs, 34,165 bp each) separated by a large (84,327 bp) and small (12,966 bp) single-copy regions. A total of 113 unique genes were predicted, including 79 protein-coding genes, 30 tRNA genes and 4 rRNA genes. The phylogenetic analysis suggested that U. rhynchophylla was closer to Neolamarckia cadamba.